Causes and impacts of domestic violence against women: Cases in Indonesia - Siregar, Wahidah Zein Br (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2024)
Domestic violence against women is still a common phenomenon in Indonesia. Data from Komnas Perempuan 2021 showed from 8,234 cases of violence against women handled by its partner institutions, 6,480 cases (79%) were happened at home. 3,221 cases of them (50%) are violence against wives. This article aims to uncover the causes and effects of domestic violence against women in Indonesia, what specific patterns are implicit in these causes, expressed by both perpetrators and victims, that could lead to a particular theory of domestic violence, and what perpetrators do to victims and what the consequences are. Using data gathered from 27 informants and 86 online news, this research finds that there are various causes of domestic violence. These causes lead to specific pattern that strengthen the use of social theories, in particular control, resource, exosystem and social isolation theories. Various forms of domestic violence done by offenders from light to heavy hits using bare hands or other tools. The impact of domestic violence can range from injury to death of the victim.